Pengaruh Rekrutmen Dan Disiplin Kerja Terhadap Kinerja Karyawan PT Inspirasi Bisnis Nusantara Jakarta Barat - Adelia Adelia; Nopi Oktavianti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
The purpose of this research is to determine the effect of rekrutmen and disiplin kerja on the kinerja karyawan of PT Inspirasi Bisnis Nusantara both partially and simultaneously. The method used is quantitative. The sample in this study consisted of 60 respondents. Data analysis employed simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis (r2), partial test (t-test), and simultaneous test (f-test). The results of this study discuss the influence of rekrutmen (X1) and disiplin kerja (X2) on kinerja karyawan (Y), as follows: the variable rekrutmen (X1) has an insufficiently significant effect on kinerja karyawan (Y), which can be seen from the correlation coefficient of 0.220, where this value falls within the interval 0.200-0.399, meaning that the two variables have a low or weak level of relationship. Based on the coefficient of determination or contribution of influence, it was 4.8%, while the remaining 95.2% was explained by other variables not discussed in this study. The variable disiplin kerja (X2) has a fairly significant effect on kinerja karyawan (Y), as indicated by a correlation coefficient value of 0.685, which lies within the interval 0.600-0.799, meaning the two variables have a strong relationship. Based on the coefficient of determination or contribution of influence, it was 47%, while the remaining 53% was explained by other variables not discussed in this study. The variables rekrutmen (X1) and disiplin kerja (X2) together have an insufficiently significant effect on kinerja karyawan (Y), which can be seen from the correlation coefficient or level of relationship between the independent variables and the dependent variable obtained at 0.272, where this value falls within the interval 0.200-0.399, meaning the two variables have a low or weak level of relationship. Based on the coefficient of determination or contribution of influence, it was 47.1%, while the remaining 52.9% was explained by other variables not discussed in this study